Core–shell structured nanoporous N-doped carbon decorated with embedded Co nanoparticles as bifunctional oxygen electrocatalysts for rechargeable Zn–air batteries. (27th January 2021) - Chen, Xiaowen; Gao, Jingxia; Wang, Luyuan; Zhu, Ping; Zhao, Xinsheng; Wang, Guoxiang; Liu, Sa
Abstract : Highly active core–shell structured PNC@CoNC was successfully prepared and used as an effective air–electrode catalyst in advanced Zn–air batteries. Abstract : Exploiting highly active and low-cost electrocatalysts is imperative and challenging for developing advanced energy storage and conversion devices. Herein, we report a core–shell structured carbon hybrid (PNC@CoNC) as an effective bifunctional oxygen catalyst prepared by a surface polymerization strategy and a subsequent pyrolysis process, consisting of nanoporous N-doped carbon core carbonized from ZIF-8 and N-doped graphitic carbon shell with embedded Co nanoparticles carbonized from the cobalt ion-doped polydopamine coating layer. The desirable nanoarchitecture endows the hybrid with a high specific surface area of 531 m 2 g −1, high conductivity, abundant micro-/meso-pores and electrocatalytically active N-dopant species. As a result, the hybrid PNC@CoNC displays a positive half-wave potential of 0.81 V towards oxygen reduction and a low overpotential of 490 mV at 10 mA cm −2 towards oxygen evolution in alkaline electrolytes, as well as excellent electrochemical stability. The bifunctional oxygen activity is comparable with that of the commercial catalysts and the recently reported electrocatalysts. Expectedly, as an air–electrode catalyst in rechargeable Zn–air battery (ZAB), PNC@CoNC shows a high power density of 130 mW cm −2, a low charge/discharge voltage gap, and superior cycling stability. Additionally, the as-prepared hybrid also shows promising application potential in solid-state ZAB. Therefore, this work provides a lesson for the synthesis of non-noble metal electrocatalysts in advanced new energy devices.